A comparative study of membrane filtration, electrocoagulation, chemical coagulation and their hybrid processes for greywater treatment. Issue 1 (February 2021) - Ucevli, Oguz; Kaya, Yasemin
Abstract: The aim of the present work was to treat greywater using standalone and hybrid processes and to reuse the treated water for irrigation and toilet flushing. Microfiltration (MF), ultrafiltration (UF) and nanofiltration (NF) membrane processes, electrocoagulation (EC) with Al and Fe electrodes, and chemical coagulation (CC) with alum, polyaluminium chloride (PAC), ferric chloride, and ferric sulphate were performed as standalone processes. In the standalone membrane processes, the Desal 5DL NF membrane showed the lowest flux decline caused by fouling and almost the highest removal efficiency. The Fe electrode showed the best performance with a low operating cost (0.067 $/m 3 ) and disposal cost of sludge (0.019 $/m 3 ) at optimum conditions (pH: 7.5; current density: 5 A/m 2 ) in the standalone EC process. Among the standalone coagulation processes, the lowest operating cost (0.06 $/m 3 ) and high removal efficiencies of chemical oxygen demand (COD), UV254, DFZ436, and turbidity were achieved with PAC at a pH of 7.5 and coagulant dosage of 100 mg/L. The water treated with standalone processes did not meet the standards for toilet flushing water and Class A for irrigation water. Therefore, the hybrid processes using the Desal 5 DL NF membrane‒BW 30 reverse osmosis (RO) membrane, Fe electrode‒Desal 5DL NF membrane, and PAC coagulant‒Desal 5DL NF membrane were performed to improve water quality. All the hybrid processes provided high‒quality water for toilet flushing purposes. The quality of the water treated with hybrid processes was determined as Class A. In addition, Class II for drip irrigation was achieved using the Fe electrode‒NF and PAC coagulant‒NF hybrid processes. However, water treated using the two‒step membrane process was not suitable for irrigation. Graphical Abstract: ga1 Highlights: Desal 5DL membrane had the lowest flux decline caused by fouling. Fe electrode showed low operating cost and disposal cost of sludge. Polyaluminium chloride showed the low operating cost and high removal efficiency. Water for drip irrigation and toilet flushing was provided with hybrid processes. Hybrid membrane process showed good performance to obtain toilet flushing water.